9.2k views
5 votes
Simplify the expression 6 - 6f + 7 - 3f - 9

User Alpana
by
5.8k points

2 Answers

3 votes

Answer:

4 - 9f

Explanation:

( 6 + 7 - 9 ) + ( - 6f - 3f ) = 4 - 9f

User Forzaa
by
5.6k points
1 vote

Answer:

Step-by-Simplifying

6 + -6f + 7 + -3f + -9

Reorder the terms:

6 + 7 + -9 + -6f + -3f

Combine like terms: 6 + 7 = 13

13 + -9 + -6f + -3f

Combine like terms: 13 + -9 = 4

4 + -6f + -3f

Combine like terms: -6f + -3f = -9f

the answer is 4 + -9f

User Asiansaga
by
4.6k points